Effects of a 3‐week dehydroepiandrosterone administration on sleep, sex steroids and multiple 24‐h hormonal profiles in postmenopausal women: a pilot study. (23rd April 2013) - Caufriez, Anne; Leproult, Rachel; L'Hermite‐Balériaux, Mireille; Kerkhofs, Myriam; Copinschi, Georges
Summary Objective Dehydroepiandrosterone (DHEA) administration is widely evocated as a 'fountain of youth', but previous studies have provided inconsistent results. We aimed to investigate in healthy postmenopausal women the effects of a 3‐week oral DHEA administration on individual steroid levels, multiple 24‐h hormonal profiles and sleep architecture. Design Seven healthy nonobese postmenopausal women, off hormone replacement therapy for ≥2 months, were investigated in a randomized, crossover, double‐blind, placebo‐controlled study. For 3 weeks, subjects took daily at 2300 h a capsule of either 50 mg DHEA or placebo. Sleep was polygraphically recorded during the last two nights, and blood samples were drawn at 15‐min intervals during the last 24 h. Results Under DHEA, testosterone and estradiol levels were increased in all individuals. Individual increments were highly variable, not related to each other, and were not related to placebo values. However, the testosterone to estradiol ratio was markedly increased under DHEA. DHEA administration had little, if any, effect on thyroid function, GH secretion, prolactin, ACTH and cortisol profiles. DHEA effects on sleep appeared to be mediated by its conversion to androgens and oestrogens: sleep quality was enhanced by increments in testosterone and dampened by increments in estradiol levels. Conclusion As DHEA‐induced elevations in testosterone and estradiol levels varied widely between individuals and were largely unpredictable, DHEA administration might not be the most appropriate approach to compensate for the reduction observed in androgen and oestrogen production in postmenopausal women. DHEA supplementation may result either in sleep stimulation or in inhibition, depending on the ratio between DHEA‐induced increments in testosterone vs estradiol.